Advances in Systems Immunology and Cancer (2014)
Aims and Scope: The Research Topic is designed to feature the latest innovative and leading-edge research, reviews and opinions on the study of complex and dynamic processes related to the mammalian immune system and cancer. All papers were meticulously selected to present our readers the multidisciplinary approach to tackle the existing challenges faced in these important fields. From high throughput experimental methodologies to computational and theoretical approaches, the articles are intended to introduce physicists, chemists, computer scientists, biologists and immunologists the idea of systems biology approach to the understanding of mammalian immune system and cancer processes. Attention was given to works that developed more effective approaches to the treatment of proinflammatory disease and cancer. The strong interdisciplinary focus will discuss biological systems at the level from a few molecules to the entire organism. Specific focus domain includes: Innate and adaptive immunity, cancer and cancer stem cell, genomic, proteomic and metabolic analysis, imaging, biophysics of immune and cancer response, computational modeling, non-linear analysis, statistical analysis, translational and disease models Types of articles: Viewpoint, commentaries, research letters, research articles, review and methodologies